Spiritual-Based Entrepreneurship Education for Early Childhood: Lesson from Indonesia - Rohmah, Lailatu; Rahayu, Dika Putri; Latif, Muhammad Abdul (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
Entrepreneurship education in early childhood has been applied to several kindergartens in Indonesia. However, some children still think that these activities are limited to playing games and have not lived up to the meaning of entrepreneurial values. This study aims to describe spiritual-based entrepreneurship education in early childhood. This research method is a qualitative case study. The research subjects were early childhood children at the Khalifah Kindergarten in Yogyakarta, aged 4-6 years. Collecting data in this study by in-depth interviews, participant observation, and documentation. Data analysis used the Miles and Huberman model with interactive analysis through data reduction, presentation, and conclusions. The results showed that spiritual-based entrepreneurship education in early childhood is an activity that can instill entrepreneurial values, increase the development of children’s religious and moral values, and form pious, honest, and challenging Muslim entrepreneurs. Spiritual activities that support entrepreneurship education at Khalifah Kindergarten Yogyakarta are alms after-market day activities, dhuha prayer, sunnah fasting, talking about the example of the prophet Muhammad as an honest entrepreneur. Entrepreneurship activities are in the form of playing activities in the classroom and outside the classroom, internal and external market days, outing classes to entrepreneurial places, and mosques. This research contributes to the understanding of entrepreneurship education in early childhood that combines entrepreneurship education with Tauhid education to instill entrepreneurial values and foster the spiritual development of early childhood to form spiritual entrepreneurs who are pious individuals and pious socially.